Development Of Nahwu Learning media based on Android - Asrori, M. Khairil; Triyono, Mochammad Bruri (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to develop Nahwu learning media to improve the teaching process of students. The method used in this investigation was ADDIE (research and information gathering, planning, development of a preliminary product form, preliminary field test, main product review, main field test, operational product review, operational field test, final product review, and dissemination and implementation). The study population consisted of 30 students of the Arabic language in experimental and control classes. Data were analyzed using the t-test. and show that Nahwu learning media are "very good", feasible to use and have been developed quite effectively to improve student learning.